Radical Organization Theory: An Incomplete Contract Approach to Power and Organizational Design - Denrell, J (2000)
A typical argument in Marxist and radical writings on economic organization is that prevailing practices, rather than being the most efficient, have been adopted in order to increase the share of the surplus of capitalists. Using an incomplete contract approach, this article develops a model which demonstrates how and when adopting an inferior economic organization could be profit maximizing. This model makes possible a detailed discussion of the conditions under which Marxist and radical claims about, for example, `deskilling', can be expected to hold. It is demonstrated that such claims could be derived using standard formal economic arguments. However, the model also shows that these claims are likely to be valid only under certain circumstances.